(untitled) (Research, Society and Development, 2022)
The objective was to identify and characterize trends in Brazilian scientific production on the health of adolescents and young people living in the Brazilian rural context. Bibliographic study, of the narrative review type, carried out from a documental analysis of abstracts of productions available in the Catalog of Theses and Dissertations of the Portal for the Coordination of Improvement of Higher Education Personnel developed with rural adolescents and young people in Postgraduate Programs in institutions Brazilians. The survey of studies was carried out in December 2021 and the information was organized and systematized in spreadsheets in Microsoft Excel 2010 software. The productions were submitted to content analysis. The corpus of analysis consisted of 16 abstracts, with a predominance of dissertation studies (81%), with productions that started in 2004, from the Federal University of Pelotas (19%) and the Federal University of Bahia (19%), with a predominance of in the epidemiology area of ​​concentration (25%). The surveys were mostly quantitative (69%) and transversal (56%). In relation to trends in knowledge, two categories emerged: characterization of dissertations and theses related to adolescents and young people in the rural context and trends in knowledge about the health of adolescents and young people living in rural areas. It is concluded that the theme is incipient and addresses important issues as well as the complexity of experiencing adolescence and youth in rural areas. Health risks related to life habits, health conditions, culture, access to and use of services, sexuality and violence are highlighted.